2015
DOI: 10.1039/c5ta01776a
|View full text |Cite
|
Sign up to set email alerts
|

Highly porous N-doped carbons impregnated with sodium for efficient CO2 capture

Abstract: Highly porous sodium-impregnated and N-doped carbon sorbents (SNSs) were prepared by KOH activation of polyacrylonitrile (PAN), followed by NaOH impregnation of the activated N-doped carbons. These new types of materials were investigated as sorbents for CO 2 capture. Particularly, SNS2-20 prepared with the KOH/PAN ratio of 2 at 700 C and 20 wt% NaOH based on the weight of the activated carbon exhibited the adsorption capacity of 6.84 and 4.48 mmol g À1 at 0 and 25 C under ambient pressure. Among the carbon so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 69 publications
1
41
0
Order By: Relevance
“…34,43 It is interesting to note that the ratio of N-5':N-6 decreased with increased activation temperature (Table S4). This is caused by a rearrangement in the C-N bond to a more thermodynamically stable state (N-6) under elevated temperature 41 45 To further elucidate the existence of such strong adsorption site within the carbon framework, we calculated a virial plot of CO 2 adsorption (Fig. S17).…”
Section: Effects Of Sorbent Chemical Compositionmentioning
confidence: 99%
“…34,43 It is interesting to note that the ratio of N-5':N-6 decreased with increased activation temperature (Table S4). This is caused by a rearrangement in the C-N bond to a more thermodynamically stable state (N-6) under elevated temperature 41 45 To further elucidate the existence of such strong adsorption site within the carbon framework, we calculated a virial plot of CO 2 adsorption (Fig. S17).…”
Section: Effects Of Sorbent Chemical Compositionmentioning
confidence: 99%
“…This enhancement is ascribed to the dipole-quadrapole interactions between the nitrogen functionalities and the CO 2 molecules. [39,40] The relative magnitude of the enhancement is far less profound at high pressures. For example, for a pore width of 0.7 nm, NQ enhances the CO 2 density by 83% compared to perfect graphite at 0.15 bar (Figure 5d inset), while it only raises the density by 3% at 30 bar.…”
Section: Effects Of Pore Size and Nitrogen Functionalitiesmentioning
confidence: 99%
“…The possible chemical structure of the graphitic matrix containing nitrogen is depicted in Figure a) . Three main species are present in all three samples: quaternary‐N (QN) 401.4±0.3 eV, pyridine‐ N ‐oxide (PNO) 402.8±0.3 eV, and pyridine (P) 398.7±0.3 eV . The XPS results are shown in Figure b)–d) for S1, S2, and S3, respectively, and they confirm the presence of a trend at increasing oxidation temperature.…”
Section: Thermal Treatmentmentioning
confidence: 55%
“…Moreover, the ternary‐coordinated nitrogen in the cyanide group permits some extent of chemisorption due to its partial basicity, without the necessity for high heat of regeneration, as it is required for amines . Several studies have shown that different nitrogen‐bearing species are formed depending on the temperature applied during the heat treatment and that their chemical nature influences the extent of CO 2 capture …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation